The Effect of Electroacupuncture Therapy with a Combination of Noni Herbs on Lowering Blood Pressure in Hypertension Cases at Ja'far Medika Hospital, Karanganyar - Aisya, Agnes Liza Nur; Prasetya, Hanung; Badri, Sholichan; Yatmihatun, Sri; Ma'ruf, Ibnu Jafar (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Hypertension is one of the main risk factors for cardiovascular disease, whose prevalence continues to increase. Electroacupuncture therapy with a combination of noni herbs can be an alternative treatment option in lowering blood pressure in patients with hypertension. This study aims to determine the effect of electroacupuncture therapy with a combination of noni herbs on lowering blood pressure in patients with hypertension at Ja'far Medika Hospital, Karanganyar. This study used a “Quasi-Experimental” research design with the Non-equivalent two-group pretest-posttest design method. with a purposive sampling method. This design uses a non-randomized trial in each experimental group Pretest was given to research subjects before intervention, and posttest was given to research subjects after intervention. The number of samples used was 34 research subjects which were then divided into 2 control groups and experimental groups. The results of the Mann-Whitney test showed that there were changes in systolic blood pressure p=0.022 and diastolic blood pressure had a value of p=0.023 which showed significant differences between the two groups, with the intervention group (electroacupuncture with a combination of noni herbs) showing more significant changes compared to the control group (sham electroacupuncture) Wilcoxon test showed a statistically significant decrease in blood pressure in both groups (p<0.001). Electroacupuncture therapy with a combination of noni herbs has more effect on reducing systolic and diastolic blood pressure in hypertensive patients at Ja'far Medika Hospital, Karanganyar.